Pancreatitis and diabetic ketoacidosis in an adolescent treated with sertraline - Ferreira, Ana Maria (2020)
Acute pancreatitis (AP) is a rare entity in pediatric age. Reports of AP in the context of diabetic ketoacidosis (DKA) have established the role of transient hyperlipemia as a consequent factor. Pharmacological etiology is responsible for 0.3−1.4% of AP cases, with no case reports of an association with the use of sertraline in the pediatric population to date. Herein is described the case of a 15-year-old girl with poorly controlled type 1 diabetes, taking sertraline for a depressive disorder, who developed AP associated with DKA. With this report, the authors intend to emphasize the importance of diagnosing AP in DKA setting. In addition, since the patient had normal serum triglyceride levels and no other risk factors for AP, it is hypothesized that sertraline may have been a triggering event in this context.